PEDAGOGICAL-PSYCHOLOGICAL FOUNDATIONS OF ADAPTIVE DESIGN COMPETENCE IN ENGINEERING EDUCATION - Kulmuradov Dilshod Istamovich (International Scientific and Current Research Conferences, 2024)
The rapid evolution of technology and increasing complexity of engineering challenges necessitate a fundamental shift in engineering education paradigms. This article examines the pedagogical and psychological foundations of adaptive design competence, a critical capability for modern engineers to respond effectively to dynamic problem-solving contexts. Through analysis of constructivist learning theories, cognitive flexibility frameworks, and metacognitive strategies, this study establishes a theoretical foundation for developing adaptive design competence in engineering students. The findings suggest that integrating adaptive design principles into engineering curricula requires a multifaceted approach combining experiential learning, reflective practice, and systematic development of metacognitive skills.